THE EFFECT OF LEARNING CYCLE 5E ON GLOBAL WARMING THEME TO ENCOURAGE STUDENTS’ SCIENTIFIC PROCESS SKILLS - Nurma Yuniarsih; Yuni Arfiani; Muriani Nur Hayati (JURNAL PENA SAINS, 2020)
This study aimed to determine the effect of the Learning Cycle 5E model on junior high school students' science process skills. This study used the Quasi-Experimental Design study with Nonequivalent control group design. The instrument used a science process skills test. The research sample is students in class VII semester II of Junior High Scool 8 Pekalongan, which purposive random sampling technique. The data were collected by essay tests of science process skills, observation sheets, and documents. Analytical data were used instrument analysis, pretest, and posttest of science process skills, etc. Based on the value of n-gain from Learning Cycle 5E class were obtained 66.33 with moderate criteria, so the Learning Cycle 5E model is moderate in science process skills. The students' responses towards the  Learning Cycle 5E model were positive, 14 of the 15 statement items included in the excellent category. It indicates that the learning cycle 5E can encourage students’ science process skills.